Perception Towards Audit Reforms - Gurunathan, Rema (2002)
The research seeks to identify the audit reforms that are agreeable to the accounting profession as well as those reforms that are not agreeable to the accounting profession in Malaysia. Questionnaires were utilized in order to gauge the perception of the accounting profession.